Workplace Experience of International Students in Australia - Barton, Georgina; Hartwig, Kay (Journal of International Students, 2020)
For the past three years over 400,000 international students have enrolled annually to study in higher education contexts in Australia (Australian Government, 2019). The extensiveness of international student enrolments has been equalled to Australia’s third highest export industry after coal and iron ore (Grewal & Blakkarly, 2017). Given the significance of international students it is important that Australian universities find effective and culturally-appropriate ways to support this cohort. One such area needing support is work experience as many study programs that international students undertake include compulsory or elective courses involving assessed experiences in professional contexts. Degrees such as business, education, engineering, health including nursing and psychology all require students to successfully complete workplace experiences in order to graduate. It is critical that international students are supported before, during and after workplace components of study as the International Student Barometer indicated that international students desire quality career advice, work experience and subsequently employment as a result of their studies (Garrett, 2014). This short essay shares brief findings from a federally funded, large-scale project carried out in Australian universities – the Work-placement for International Student Programs (WISP) project. The WISP project aimed to investigate international students’ experiences in workplace contexts, but also their preparedness for such experiences. Data was collected from six universities including international student, workplace and university staff interviews; university documents; and international students’ assessed reports from their work experience. In addition, a large scale survey was also distributed across Australia – whereby findings are reported in Barton, Hartwig and Le (2017). Findings from the qualitative data showed that international students face different challenges on work experience as compared to their domestic counterparts. Issues such as language difference, financial difficulties, being away from usual support networks, and cultural difference related to professional skills were identified. We theorised that international students indeed encounter ‘multi-socialisation’ (Barton et al., 2017) whereby they are expected to socialise into a new country, new university context, and workplace environment. Further, our extensive data showed that many work place staff have limited capacities in cultural awareness and hence diverse approaches to working with, and supporting,international students. In fact, some work place staff showed hesitation in hosting international students as they perceived them as being ‘hardwork’ (Barton, Hartwig, Joseph & Podorova, 2017). Conversely, our data showed the success many that international students experience during work placement. For work place staff who displayed high ‘ethos’ (Knight, 1999), huge benefits in hosting international students were experienced for both parties. Another major finding was that international students often find reflecting on their practice and consequently putting new practice into place challenging. Of course, this may be an issue for all students however, our international student participants noted reflecting on challenges and knowing how to improve action was difficult, particularly if their host was not supportive. Conversely, supportive hosts modelled good practice and worked above and beyond to support international students to success. Recommendations from the WISP project are outlined in Table 1 below: Table 1: Recommendations for all stakeholders in relation to work experience for international students International students University Staff (includes academic support staff) Work place supervisors and staff Know and use the range of support services available at your university for international students. Learn about and experience new cultural and professional contexts through volunteering. Be involved in any university learning activities that will assist you to reflect and understand Australian workplace contexts. Participate in a community of learners by sharing your expertise, cultural knowledge and skill sets with the university, workplace and your peers. Regularly seek your supervisor’s feedback on your performance and ensure you understand and can implement this advice. Organise a meeting with international students and their supervisor prior to work placement, as well as post-placement sessions with university staff. Encourage international students to gain experience in new cultural and professional contexts through volunteering. Include a range of teaching and learning activities such as role plays, videos and critical reflection to assist international students’ understanding of Australian workplace contexts. Create a community of learners through multimedia to encourage communication during work placement. Share responsibility of feedback and assessment to allow a fuller understanding of the student’s progress. Create a welcoming workplace environment including a student work space, clear expectations and open lines of communication. Embrace and utilise international students’ unique cultural knowledge and experience in your workplace. Include a diverse range of communication techniques to explain key concepts about the workplace context. Encourage international students to become involved in the wider workplace community. Provide international students regular feedback and demonstrate strategies for improvement and check for understanding. Our project resulted in a conscious focus on positive aspects of international students’workplace experience given the negativity that is often portrayed in the literature. Such a strengths-based approach allowed us to report on ways that worked in supporting both international students and their hosts, ensuring increased employability and reflexive professionals upon graduation.